Tradition as Translation: The Byways of Symbolism in Folktales - Vaz da Silva, Francisco (16th Congress of the International Society for Folk Narrative Research, 2013)
This paper explores a specific point in the dynamics of folktale transmission. It calls attention to the facts that the Latin term traducere means to convey across as well as to translate linguistically, and Lat. tradere means “to betray” as well as “to transmit.” Then, the discussion explores the possibility that these puzzling traits may reflect the quintessence of oral traditions. In oral settings, any given story exists in multiple versions. Orally transmitted stories encompass multiple voices, which reflect—and often distort—one another. In other words, oral transmission hinges on matters of quid pro quo, i.e., on symbolic transpositions, which is why In tradition—as in the work of translators—the traduttore, traditore adage applies, Semantic transpositions are of the essence of symbolic creativity; in this sense, semantic translations lie at the very core of folklore dynamics.